ROLE OF BIOTECHNOLOGY IN ABIOTIC STRESS TOLERANCE IN PLANTS - ABBAS, A; RIAZ, S; WALEED, R; Ali, Q (Biological and Clinical Sciences Research Journal, 2024)
As population grows, abiotic stresses reduce plant growth and agricultural output, affecting global food security. Heat, cold, drought, salinity, and heavy metals affect crops. Heat stress from climate change disrupts cellular metabolism and lowers productivity. Tropical and subtropical crops suffer physiologically from cold stress. Climate variability affects drought, reducing crop output and germination. Salinity stunts growth and causes nutritional imbalances in big agricultural areas. Heavy metal buildup in soils threatens plant health. To overcome these problems, plants use osmotic adjustment, antioxidant defenses, and stress signaling pathways. CRISPR/Cas9 and other genetic engineering and molecular breeding methods may improve crop stress tolerance. Using omics technologies (genomics, transcriptomic, proteomics, and metabolomics) in breeding programs helps us understand stress tolerance processes and generate resilient crop types. This research is crucial for sustainable agriculture and global food security.